KEBIJAKAN HUKUM PIDANA TERHADAP KEWENANGAN ODITUR MILITER UNTUK OPTIMALISASI PERCEPATAN FUNGSI PENUNTUTAN DALAM SISTEM PERADILAN PIDANA MILITER DI INDONESIA - Imam Ghozali (LPPM Universitas Bina Bangsa, 2022)
The military justice system places the military Prosecutor as one of the law enforcement parts in the military jurisdiction in the prosecution function, however, in the prevailing military justice system it allows the Case Rectifier Officer to hinder the function of the military prosecutor as a criminal law enforcer in fulfilling the principles of cheap, fast and simple criminal justice. This paper will provide an explanation of how the regulation of the authority of military prosecutors in Indonesia should be to optimize the acceleration of prosecutions in military courts with a normative juridical research approach method. After conducting research with the predetermined method, it was found that the incomprehension of the duties of military prosecutors is faced with the legitimacy of power that does not fully use a legal approach because in its implementation there is a Papera institution that can determine whether or not a TNI soldier who violates the criminal law is submitted to the military court, so as to optimize the prosecution function the authority of the military prosecutor needs to be strengthened by eliminating Papera's function in the prosecution function in the military criminal justice system to reduce the potential for allusions between military prosecutors and papera which is based on the slowness of the prosecution function